Hair Pb Levels, Work Duration and Health Complaints, of Waste Officers on Temporary Dump Site (Study on Dumpster Temporary Dump Site Mulyorejo Surabaya) - Tirtaadi Tirtaadi (JURNAL KESEHATAN LINGKUNGAN, 2017)
Hazardous household waste containing lead in TPS Mulyorejo is a source of environmental contamination that can caused health effects in humans. Heavy metals in the body will accumulate in hair, bone and soft tissue. Continuous Pb exposure would cause impacts include neurological disorders, kidney function, reproductive system, haematopoietic system, and the nervous system. The aim of this study to hair Pb levels, duration of work and health complaints officer at the temporary dump site Mulyorejo Surabaya. In this study was used a descriptive design with cross-sectional approach. The sample was 15 officer of the transport dumper in TPS Mulyorejo Surabaya and drawn by simple random sampling technique. The independent variable was the hair Pb levels and work of duration. The dependent variable is the health complaints. Hair Pb levels on the waste workers were still in the normal range between 0.007 to 1.17 mg/Nm3, although normal hair Pb levels but officers waste feel a lot of health complaints. Period and duration of working hour a day will affect the pile of Pb in hair and health complaints. Many perceived health complaints include feeling weak, fatigue, shortness of breath, diarrhea, decreased appetite, feeling dizziness, throat irritation, dizziness and back pain. Its recommended that, DKP Surabaya and RT/RW increase cooperation in sorting and processing waste. For officers conduct periodic inspections to determine health problems early, eating nutritious foods, vitamins, and minerals to reduce the levels of Pb in the hair.